Legal Standing of Employees as Individual Creditors in Filing for Bankruptcy of State-Owned Enterprises - Sumayya Muttaqin; Iwan Erar Joesoef (Jurnal Daulat Hukum, 2025)
This study aims to analyze the legal standing of employees as individual creditors in filing for bankruptcy against State-Owned Enterprises (SOEs), with a focus on the case study of PT Merpati Nusantara Airlines (Persero) as stated in Cassation Decision Number 447 K/Pdt.Sus-Pailit/2016. This study was motivated by legal uncertainty regarding the rights of employees to file for bankruptcy against SOEs, even though they normatively meet the bankruptcy requirements as stipulated in Law Number 37 of 2004 concerning Bankruptcy and PKPU. The research method used was normative juridical with a legislative approach, case approach, and conceptual approach. Data was obtained through literature study and analyzed qualitatively deductively to examine the conformity of the judge's considerations with the provisions of Law Number 19 of 2003 concerning SOEs, Law Number 6 of 2023 concerning Job Creation, as well as the principles of justice and legal certainty. The results of the study show that the judge's considerations in rejecting the bankruptcy petition by employees are not fully in line with the provisions of the legislation, because PT Merpati has the status of a state-owned enterprise that is subject to private law and should be able to be declared bankrupt by creditors, including employees. However, the judge interpreted that Merpati's status as a state-owned enterprise with a public function prevented the bankruptcy process, which ultimately weakened the protection of workers' rights. The novelty of this research lies in emphasizing the importance of separating the public and commercial functions of SOEs and the need for consistent interpretation guidelines for judges in order to create substantive justice and legal certainty in future SOE bankruptcy cases.